PENGEMBANGAN PANDUAN PELATIHAN EFIKASI DIRI DALAM HUBUNGAN PERTEMANAN MELALUI STRATEGI EXPERIENTIAL LEARNING BAGI SISWA SMP - Rachmawati, Layli Novita; Hidayah, Nur (Jurnal Kajian Bimbingan dan Konseling, 2016)
The research aims to develop self-efficacy training guides in friendship through experiential learning strategies for junior high school students, so that the counselor can use it as a media of social guidance services for the student especially to improve his confidence in the friendship. This training guide is printed teaching materials containing substance, operational measures, and the evaluation. The procedur of this developmental research is adapted from Borg and Galls (1983) which did in 3 step; 1) plannin;(2) developmental product; and (3) try out of the product. Based on the results of data analysis from expert assessment and potential users as well as revisions that are made in accordance with the advice and input to the product, it can be concluded that this training guide meets the good acceptance criteria and effectively proven in improving students self-efficacy in peer friendships.